A discrete-modules-based frequency domain hydroelasticity method for floating structures in inhomogeneous sea conditions. (October 2017) - Wei, Wei; Fu, Shixiao; Moan, Torgeir; Lu, Ziqi; Deng, Shi
Abstract: Based on the three-dimensional (3D) potential theory and finite element method (FEM), this paper proposes a new numerical method for hydroelastic predictions of floating structures in inhomogeneous seabed and wave field conditions. The continuous floating structure is first discretized into rigid modules connected by elastic beams. The motion equations of the entire floating structure are established according to the six degrees of freedom (6DOF) motions of each module by coupling the hydrodynamics of the modules with the structural stiffness matrix of the elastic beams in the frequency domain. By applying different wave excitation forces onto different modules, this discrete-modules-based method then uniquely realizes application of various wave excitation forces onto different modules of the structures in inhomogeneous waves. The hydroelastic responses of a plate and a Wigley hull under an even and uneven seabed using the proposed method are verified against the results from the published model tests and the conventional 3D hydroelastic method. Finally, the effects of inhomogeneous waves on the distributions of the bending moment, shear force and vertical displacements of the freely floating plate are investigated. The results show that the inhomogeneity of waves may induce about 2 ∼ 3 times increase of the force responses in a specific wave frequency.